”WISATA AIR DI BALI” MENELUSURI AIR DALAM LIKA-LIKU HIDUP ORANG BALI - Ketut Sumadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Water is the immortal substance of God's creation that became the beginning of theformation and also the end of life in this universe. In the context of Balinese cultural tourism,Balinese activities in glorifying, nurturing and managing water and springs with beautiful naturalscenery are widely spread in villages can actually be managed by local people to become atourist attraction. The problem is, this activity has not been well utilized as a tourist attractionmaximally. Government and tourism entrepreneurs need to pay attention to this phenomenon, soit is necessary strategy and efforts in favor of local community in accordance with the concept ofcommunity based tourism and sustainable tourism. Because